Political change and working class formation between 1945-1960 in Turkey - Kocabaş, Erdem. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
The conditions and properties of the working class formation between the end of the Second World War and the military intervention of 1960 have not recieved the attention they deserve from scholars working in the field of labor history. This partly has been due to the obvious weakness of the labor action and union organization in the 1950s when compared to the periods of the 1960s and 1970s. At the same time, the dominant view of labor history has prevented the period from being regarded as an attractive subject of study. The thesis tries to alter this limited approach in labor history in two ways. First of all, the selection of the period is against the general tendency of focusing on the periods where the working class is visible to the public by its colletive action as an obvious social actor. The 1950s are considered as an important period of transition in which the formation of working class accelerated, and the “amele” of the late Ottoman era became the “isçi” of modern Turkey. In addition to the choice of period, the method selected aims to go beyond the approach regarding the working class formation just as a passive result of legal regulations and economic development. An analysis of the factors affecting the class formation within their multi-level causal hierarchy and without strong deterministic relations would help us to end up with a rich checklist of working class formation in the period in question and understand the nature of the labor movement in modern Turkey.
Keywords: Working class -- Turkey.